2003
DOI: 10.1063/1.1564047
|View full text |Cite
|
Sign up to set email alerts
|

Translational diffusion of polymer chains with excluded volume and hydrodynamic interactions by Brownian dynamics simulation

Abstract: Within Kirkwood theory, we study the translational diffusion coefficient of a single polymer chain in dilute solution, and focus on the small difference between the short-time Kirkwood value D (K) and the asymptotic long-time value D. We calculate this correction term by highly accurate largescale Brownian Dynamics simulations, and show that it is in perfect agreement with the rigorous variational result D < D (K) , and with Fixman's Green-Kubo formula, which is re-derived. This resolves the puzzle posed b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
84
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 46 publications
3
84
2
Order By: Relevance
“…(2). For example, simulations in free solution 24 suggested that very long simulations, at least 100s in duration, are required to reach the asymptotic limit. As we will show later, such long simulations are infeasible for channel-confined DNA due to the cost of incorporating bead-wall hydrodynamic interactions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…(2). For example, simulations in free solution 24 suggested that very long simulations, at least 100s in duration, are required to reach the asymptotic limit. As we will show later, such long simulations are infeasible for channel-confined DNA due to the cost of incorporating bead-wall hydrodynamic interactions.…”
Section: Introductionmentioning
confidence: 99%
“…(2) and hereafter, we interpret the square of a vector as R 2 ¼ R Á R, not as a dyadic product RR. The difference between D (K) and D L has been addressed for flexible and semiflexible polymer chains in free solution, [18][19][20][21][22][23][24][25][26] with errors in the range of 1% to 25% for different approaches and different polymer models. For example, the error increases by increasing the chain size, 24 or by increasing the flexibility of the chain 26 or by reducing the solvent quality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(A1) of the form D 0 = k B T /(ξ N ), where ξ is a friction parameter. To see this term, Liu and Dünweg 72 have shown that one is to work strictly within the assumptions of Kirkwood theory so that the model exhibits clear time scale separation and, consequently, D 0 is visible at short times, but not in the long-time limit. For the sake of completeness, we performed a regression analysis for the data in Fig.…”
Section: Chain Diffusionmentioning
confidence: 99%
“…The lack of a clearly separated intermediate time scale means there is no theoretical argument that we should observe D 0 , 72 which is also the argument that Liu and Dünweg give for D 0 not being observed in MD simulations. 72 We have compared the SRD fluid parameters in Ref. 64 (such as density and viscosity) and they can be mapped to values in a similar range to ours.…”
Section: Chain Diffusionmentioning
confidence: 99%